SP betting as a self-enforcing implicit cartel - Adi Schnytzer; Avichai Snir (Bar-Ilan University, Department of Economics, 2007)
A large share of the UK off-course horse racing betting market involves winning payouts determined at Starting Prices (SP). This implies that gamblers can bet with off-course bookies on any horse before a race at the final pre-race odds as set by on-course bookies for that horse. Given the oligopolistic structure of the off-course gambling market in the UK, a market that is dominated by a small number of large bookmaking firms, we study the phenomenon of SP as a type of self-enforcing implicit collusion. We show that given the uncertainty about a race outcome, and their ability to influence the prices set by on-course bookies, agreeing to lay bets at SP is superior for off-course bookies as compared with offering fixed odds. We thus extend the results of Rotemberg and Saloner (1990) to markets with uncertainty about both demand and outcomes, We test our model by studying the predicted effects of SP betting on the behavior of on-course bookies. Using data drawn from both the UK and Australian on-course betting markets, we show that the differences between these markets are consistent with the predicted effects of SP betting in the UK off-course market and its absence from the Australian market.
Keywords: 330; Glücksspiel; Pferdesport; Oligopol; Kartell; Großbritannien; Australien